Geochemical Behaviour of Heavy Metals in the Sondong Region of Bacgiang, Vietnam: A Comprehensive Case Study - Niem, Nguyen Van; Viet, Bui Huu; Nguyen, ?o ?uc; Vu, Ph?m Nguyen Ha; Trung, Nguyen Minh; Blokhin, Maksim; Trung, Bui Bao; Ha, Nguyen Thi Hoang; Tran, Tuan Anh (International Journal of Membrane Science and Technology, 2024)
Characterizing geochemistry is crucial for identifying pollutant sources and providing a scientific basis for environmental control and management. This study aimed to determine the geochemistry of stream water and sediment and metal sources for environmental management of the Luc Nam River basin in the Son Dong area, Bac Giang province, Vietnam. The results revealed geochemical background (GB) and minimum anomalies (MA) of Cu, Pb, Zn, Hg, and pH in water and Cd, Hg, and Cu in sediment. The highest anomalies in stream water were pH (4.2), Zn (63.7MA), Cu (5.7MA), Mo (3.7MA), Hg (3.4MA), Sb (2.0MA), Pb (1.2MA) and As (1.6MA). The highest anomalies in sediment were Pb (1.6MA), Cd (1.2MA), Cu (1.1MA), Ni (1.6MA), Hg (1.9MA) and Co (1.1MA). Based on the geochemistry of water and sediment, three zones were characterized: (1) Zone I: a natural source with recognized copper mines (Lang Lan, Giao Liem, An Lap, and Yen Dinh) and possible unrecognized mines; (2) Zone II: natural and anthropogenic sources from exploited mines (i.e. Khuon Muoi, Dong Bua, and Bien Dong) and deposits that have not been exploited (Phu Nhuan and Tan Thanh copper deposits, Lang Vai gold deposit); and (3) Zone III: natural source with possible unrecognized mines. These findings contribute to understanding the behavior of elements in response to governance changes in the environmental composition of water and sediments, which can affect ecosystems and communities beyond just the environmental standards and regulations of the government.